Development of a Mobile Web Information System for Ordering and Managing Local Products - Nafis Fausta Zaki; Arief Hermawan (bit-Tech, 2025)
Digital transformation is essential for enhancing operational efficiency, minimizing errors, and increasing transparency, particularly for small and medium-sized enterprises (SMEs). This study investigates the operational challenges faced by Parfum ARX+, a local SME engaged in the perfume industry, which relies on manual ordering and inventory management systems that often lead to service delays, stock inaccuracies, and workflow inefficiencies. To address these issues, this research proposes the design and development of an integrated web-mobile information system aimed at automating order placement, stock control, and sales reporting. The system includes core features such as user registration, dynamic product catalog, real-time inventory updates, digital payments, and administrative dashboards. It was developed using Flutter for mobile applications, React for the web interface, and Firebase for backend services including real-time database and secure user authentication. System evaluation was conducted through black-box testing to assess functional reliability and user experience under operational conditions. The results show that the system successfully met all functional requirements, significantly reducing order processing time by approximately 35%, improving inventory accuracy, and enhancing overall administrative performance. By enabling real-time data access and automated transactions, the system improves customer satisfaction and supports data-driven decision-making for business managers. This research demonstrates how low-cost, scalable digital platforms can transform conventional business operations into efficient, user-friendly, and transparent systems, contributing to improved competitiveness and operational resilience among SMEs. The system serves as a model for similar enterprises seeking to implement digital solutions in order to adapt to evolving market demands and technological developments.